2017
DOI: 10.1071/ah16009
|View full text |Cite
|
Sign up to set email alerts
|

Beyond clinical priority: what matters when making operational decisions about emergency surgical queues?

Abstract: Objective. This paper describes the perceptions of operating theatre staff in Australia and The Netherlands regarding the influence of logistical or operational reasons that may affect the scheduling of unplanned surgical cases. It is proposed that logistical or operational issues can influence the priority determination of queue position of surgical cases on the emergency waiting list.Methods. A questionnaire was developed and conducted in 15 hospitals across The Netherlands and Australia, targeting anaesthet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(10 citation statements)
references
References 12 publications
0
10
0
Order By: Relevance
“…In their observational studies, Lin et al (2022) and Blanch et al (2016) found that there was little guidance or evidence for how to prioritise patients who have the same triage ranking. This scoping review supports the need for clear guidelines that should be implemented into hosptial policy and emphasises the importance of understanding factors influencing clinical prioritisation in scheduling semi-urgent surgeries (Ax et al, 2019;Bhattacharyya et al, 2006;Fitzgerald et al, 2006;Fitzgerald & Wu, 2017;Leppäniemi & Jousela, 2014). The lack of consensus and guidance in clinical prioritisation for semi-urgent surgeries poses a significant risk to patients, surgical teams and departments.…”
Section: Discussionmentioning
confidence: 59%
See 4 more Smart Citations
“…In their observational studies, Lin et al (2022) and Blanch et al (2016) found that there was little guidance or evidence for how to prioritise patients who have the same triage ranking. This scoping review supports the need for clear guidelines that should be implemented into hosptial policy and emphasises the importance of understanding factors influencing clinical prioritisation in scheduling semi-urgent surgeries (Ax et al, 2019;Bhattacharyya et al, 2006;Fitzgerald et al, 2006;Fitzgerald & Wu, 2017;Leppäniemi & Jousela, 2014). The lack of consensus and guidance in clinical prioritisation for semi-urgent surgeries poses a significant risk to patients, surgical teams and departments.…”
Section: Discussionmentioning
confidence: 59%
“…Studies were conducted in several countries (Figure 2) with most undertaken in Europe ( n = 9) (Ax et al., 2019; Cardoen et al., 2010; Fitzgerald & Wu, 2017; Koivukangas et al., 2020; Leppäniemi & Jousela, 2014; Sandbaek et al., 2014; van Veen‐Berkx et al., 2016; Wullink et al., 2007; Zonderland et al., 2010). Across the 12 research articles, study characteristics are reported in Table 3.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations